Novel Pathologic Finding of Digital Soft Tissue Chondroma in a Child: A Case Report and Review of Literature. (October 2015) - Rubin, Todd; Schwartz, Andrew; Fornari, Eric; Schulz, Jacob
Unlike osteochondromata that develop in the hand, soft tissue chondromata (STC) devoid of bone and tendinous attachments are exceedingly rare. They have been described in adult patients of middle age, though have not been previously reported in the pediatric population. We report the case of a 9-year-old female that presented with a tender digital mass 6 months following a minor hand injury. After an extensive workup, the mass was surgically excised and diagnosed as an STC. Our case is the first to identify a digital STC in a pediatric patient and expands on the pathologic differential diagnosis. While the true incidence in the pediatric population is unknown, STC should be included in the differential diagnosis when any patient, adult or child, presents with a digital mass.